2016
DOI: 10.26719/2016.22.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of core and support functions of case-based surveillance of meningitis in hospitals in Khartoum state in 2015

Abstract: Case-based surveillance of meningitis was implemented in Khartoum State in February 2013 but its implementation has not been evaluated. This study assessed some core (case confirmation) and support (case reporting and investigation resources) functions of case-based surveillance of meningitis at hospital level in Khartoum State, Sudan, from January to March 2015. An interview questionnaire and checklist were used to collect data from 31 hospitals. A poster containing the case definition of meningitis was fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 2 publications
6
14
0
Order By: Relevance
“…Case confirmation. Four of the 30 reviewed studies recommended strengthened case confirmation capacities [19,36,38,39]. Of these, two studies reported that prompt public health action requires enhanced laboratory capacity [19,36].…”
Section: Core Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Case confirmation. Four of the 30 reviewed studies recommended strengthened case confirmation capacities [19,36,38,39]. Of these, two studies reported that prompt public health action requires enhanced laboratory capacity [19,36].…”
Section: Core Functionsmentioning
confidence: 99%
“…Similarly, laboratory capacity strengthening and prompt specimen collection was recommended in Ghana to ensure adequate surveillance and response preparedness to Ebola [39]. A sub-theme based on a recommendation derived from the reviewed studies alluded to improved specimen handling [38]. Functions relating to case https://doi.org/10.1371/journal.pone.0248998.g001…”
Section: Core Functionsmentioning
confidence: 99%
See 3 more Smart Citations